Characterization of antimicrobial susceptibility, extended-spectrum β-lactamase genes and phylogenetic groups of Shigatoxin producing Escherichia coli isolated from patients with diarrhea in Iran - Erfaneh Jafari; Mana Oloomi; Saeid Bouzari (BMC, 2021)
Abstract Background Shiga toxin‐producing Escherichia coli (STEC) are among common foodborne bacterial pathogens and healthy livestock are the main source of this bacterium. Severe diseases attribute to two types of cytotoxin Stx1 and Stx2, which are also called Shiga toxin (Stx). Infection of humans with STEC may result in Acute diarrhea with or without bleeding, hemorrhagic colitis (HC) and the hemolytic uremic syndrome (HUS). As antibiotic resistance is increasingly being reported among STEC isolates obtained from livestock and patients worldwide, in this study the pattern of antibiotic resistance in clinical isolates was determined. Methods Stool samples were collected from patients with diarrhea. All samples were cultured and identified by biochemical and molecular tests. Antimicrobial susceptibility test and assessment of extended-spectrum β-lactamase (ESBL)-related genes were conducted. Moreover, phylogenetic groups were analyzed using quadruplex PCR, and DNA analysis assessed multi-locus sequence types (MLST). Results Out of 340 E. coli samples, 174 were identified as STEC by PCR. Antimicrobial susceptibility test results showed that, 99.4%, 96% and 93.1% of isolates were susceptible to imipenem/ertapenem, piperacillin-tazobactam and amikacin, respectively. The highest resistance was towards ampicillin (68.4%), followed by trimethoprim-sulfamethoxazole (59.8%), and tetracycline (57.5%). A total of 106 (60.9%) isolates were multidrug resistance (MDR) and 40.8% of isolates were determined to be extended spectrum β-lactamase producers. In 94.4% of isolates, genes responsible for ESBL production could be detected, and blaTEM was the most prevalent, followed by blaCTX-M9. Furthermore, phylogenetic grouping revealed that majority of STEC strains belonged to Group C, followed by Groups E, B2 and A. MLST unveiled diverse ST types. Conclusion A periodical surveillance studies and thorough understanding of antibiotic resistant profiles in STEC isolates could help select effective antibiotic treatment for patients and develop strategies to effectively manage food contamination and human infections.